Precision validation of MIPAS-ENVISAT products - Piccolo, C; Dudhia, A (2007)
This paper discusses the variation and validation of the precision (defined as the dispersion of an ensemble of retrievals obtained from measurements of the same atmospheric state) of the ESA L2 products from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS). The MIPAS L2 products contain estimates of random error derived from the propagation of the radiometric noise through the retrieval. The noise itself varies with time, steadily rising between decontamination events, but its contribution to the L2 random error also depends on the atmospheric temperature, which controls the total radiance received. Hence, for all species, the random error varies latitudinally/seasonally with atmospheric temperature, with a superimposed time dependence on decontamination events. The precision validation involves comparing two MIPAS retrievals at the intersections of ascending/descending orbits. For every 5 days per month of high resolution MIPAS operation, the standard deviation of the statistic of the matching profile pairs is computed and compared with the predicted random error given in the MIPAS Offline L2 data. Even taking into account the propagation of the pressure-temperature retrieval errors into the VMR retrieval, the observed scatter is usually a factor 1-2 larger than the predicted error. This is thought to be due to effects such as horizontal inhomogeneity of the atmosphere.